THE IMPACT OF COVID-19 PANDEMIC ON SOCIOLOGY LEARNING AT SMA NEGERI 2 KUPANG - Hermina Neam (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
The purpose of this study was to determine the learning process in the classroom through the probing-prompting method. In this study, the method used a literature study which consisted of four stages, namely collecting literature data, selecting relevant literature, conducting a review, and concluding or providing a new interpretation. The data collection technique was carried out online by downloading literature in the form of journals or articles through Google Scholar with the keyword probing-prompting and obtaining 113 literature data. The results of this literature study stated that the probing-prompting method in classroom learning was more effective than conventional learning methods. Efforts made to achieve optimal learning in the classroom can be achieved through the foresight of teachers to choose learning methods that provide space for students to always actively participate and develop their potential. One of the appropriate methods is the probing-prompting method seen in the development of student communication, increased creative thinking, increased critical thinking, can instil learning concepts, and can improve student learning outcomes.